Schutz's Phenomenological Study on Debtors of the Gapura Karomah Program, Tanah Laut Regency, Indonesia - Lestari, Nisrina Ayu; Abdurrahman Sadikin (Open Access Indonesia Journal of Social Sciences, 2023)
Gapura Karomah is a loan program run by the Bank Perkreditan Rakyat (BPR) Tanah Laut with zero percent (0%) interest for people who have difficulties in terms of capital. This research focuses on debtors of the Gapura Karomah program who make smooth payments of credit return obligations even though there is no collateral provided. The purpose of this research is to find out the motives for the reasons and the motives for the benefits of the debtor to make smooth payment of loan repayments even without collateral and to analyze how the debtor maintains the trust of the BPR and the Tanah Laut Regency Government. This study is qualitative research that explores and describes in detail a situation or phenomenon of the research object studied by developing concepts and gathering existing facts using the Schutz Phenomenology approach. This phenomenology analyzes research findings through themes originating from the presentation of data that can provide an overview of the motives for the causes and benefits of the debtor. The results of the study show that BPRs provide a program, namely Gapura Karomah, by providing credit without interest and without collateral but through a long process. The causal motives are the intention to make payments on time, have other income from other business sources, and have good financial management. The benefit motive is to help develop a business with capital obtained from credit and maintain the good name of the debtor for ease of applying for credit in the future. The way the debtor maintains the trust of the BPR is by setting aside any income from the main operating results as well as from other sources of business income.